New Business Models in Agroecology: Study Case - Innovation Hub Bio Danubius as Private (Voluntary) Standards Based on Indicators - Lianu, Costin; Radulescu, Irina Gabriela; Lianu, Cosmin (Annals of Spiru Haret University. Economic Series, 2024)
Agroecology is a new area of knowledge and emerging body of experience linking in a transdisciplinary manner, experiments, research, and action-oriented innovations targeting enhanced food systems’ resilience, environmental and socio-economic sustainability at the farm, organizational and institutional levels. Authors view is that applying ecological principles and social values to agricultural production and consumption has to have a market recognition. This paper investigates in which conditions agroecology can also offer new business models that are more inclusive, diverse, and profitable for farmers and other food system actors especially those small farmers actioning in a regional context and willing to cooperate to co-create new business models. These business models involve the adoption of innovations such as integrated management, organic fertilizers, participatory guarantee systems, and collective marketing in a regional value chain perspective. The paper investigates as well some pathways to agroecology developed in IH Bio Danubius, a regional cluster already engaged in organic agricultural practices and willing to further embrace new agroecological principles. One important pathway, in wich our research is conducted are conditions under which private (voluntary) standards based on indicators can meet market requirement through a viable business model.